ASSEMBLEIAS DE ANFÍBIOS ANUROS, USO DO TEMPO E DO ESPAÇO EM DUAS ÁREAS DE FLORESTA OMBRÓFILA MISTA, SUL DO BRASIL - REYNAUD, CAMILA CHAPIESKI (2016)
The Anura order comprises 129 species recorded in the Araucaria Forest phytophysionomy (FOM), but this is a little known kind of forest, with large sampling gaps, showing a need to make inventories. Thus, this chapter describes the assemblies of amphibians the Jardim Botânico Faxinal do Céu (FC), Pinhão municipality, Paraná and Parque Municipal São Francisco da Esperança (SF) Guarapuava municipality, Paraná, analyzing richness patterns, composition and constancy of species between areas and comparing them with other assemblies already known in FOM sites. For data sampling, the active search method was used, visual and audibly oriented, with a sampling effort of 260 hours / person for 29 nights of sampling to CF and 225 hours / person for 25 nights to SF, between August 2014 and October 2015. The areas varied in richness and species composition, with exclusive species in each área. In FC area was recorded a richness of 20 species and SF, 14 species. FC showed a higher diversity index but lower equitability when compared to SF, which can be caused by the different environment structure between areas.Typical species of preserved forest habitats were identified in both areas, such as Ischnocnema guentheri and Haddadus binotatus, and also Melanophryniscus spectabilis, a species hard to register, demonstrating the importance of inventories for conservation strategies and measures, providing basis for future studies. Through the cluster analysis, it was observed that both studied areas are similar mainly with nearest studied area (Parque Municipal das Araucárias), also located in Guarapuava, Paraná. From the records of this work, including species that depended on forest habitats and the ones hard to register, the importance of these forests for the maintenance of these species can be inferred, as well as the need for inventories so that they form databases for further studies and future decisions on the group's conservation.